Studies in symbolic interaction. Vol. 34 - Denzin, Norman K. (Bingley, UK : Emerald, 2010)
Part I of Volume 34 of Studies in Symbolic Interaction contains 11 outstanding contributions by leading activist scholars on commodity racism, Chief Illiniwek, and native American sport mascots. Part II, New Interpretative Works, contains seven performance narratives: black womanhood, masculinity, whiteness, and gender, sexual violation, old civilization and democratic citizenship.
Part I: Decolonial Openings: Fashioning Narratives and Identities against/after Chief Illiniwek. Thinking against/after Chief Illiniwek / C. Richard King ; Explaining the NCAA Decision, August 9, 2005 / Carol Spindel ; Mourning the mascot's demise: on prehistoric origins and modern aftermath / Synthia Sydnor ; ''Leutwiler's Indian'': creating the ''Chief'' tradition at the University of Illinois / Jennifer Guiliano ; Why the NCAA was right / Stephen J. Kaufman ; Inventing tradition: the Garippo Report and the paraphernalia of jurisprudence / Ray Gamache ; Death and resurrection of Chief Illiniwek (1926-2007) / David Prochaska ; Staging an intervention in a virtual dystopia: the online fallout of the race, power and privilege forum and the removal of ''Chief Illiniwek'' / Cassidy C Browning ; The university of Chief Illiniwek? consuming ''indianness'' in the shadows of memorial stadium / Michael D. Giardina ; (Not) Writing about the chief / David Roediger ; On deaf ears: an activist's comments to the university's trustees / Stephen J. Kaufman -- Part II: New Interpretative Works. "Born to be wild" or a "tale of two theories": a performance of black womanhood in the United States / Amira Millicent Davis ; Romance, nostalgia, and danger: disposing of the white male guide / Richard J. Doherty ; "And her death filled her with great plentitude": whiteness, erasure, and racialized schooling / Myra Margolin ; Stepping out, speaking up: resisting sexual violence through narratives / Koeli Moitra Goel ; The chargeling / Corey Holding ; Playing with oil: putting performativity at the center of oil civilization / Daniel Lord ; Lifelong education and democratic citizenship / John M. Johnson.
Description based on print version record.
Print version record
Keywords: Symbolic interactionism; Social interaction; Indians as mascots; Sports team mascots -- Social aspects -- United States; Social interaction; Cultural studies; Language Arts & Disciplines -- Communication Studies; Social Science -- Anthropology -- Cultural; Social Science -- Anthropology -- Physical